Südtirols Minderheitenschutzsystem Grundlagen, Entwicklungen und aktuelle Herausforderungen aus völker- und verfassungsrechtlicher Sicht - Haller, Matthias (Schriften zum Völkerrecht (SVR), 2021)
»South Tyrol's Minority Protection System. Fundamentals, Developments and Current Challenges from an International and Constitutional Law Perspective« South Tyrol is a model for the resolution of minority conflicts based on a complex interplay of international and constitutional law. This book sheds light on this minority protection system from the Austro-Italian Paris Agreement in 1946 up to the present and is thus a handbook for this system. In addition, it looks at who may represent the German and Ladin minorities under international law and how limitations of the autonomy after the 2001 reform of the Italian Constitution can be reversed.